Online Food Shopping: A Conceptual Analysis for Research Propositions - Liu, Chi-Fang; Lin, Chien-Ho (Frontiers in Psychology, 2020)
Shopping foods online is different from shopping other things online. To stimulate more thinking and enrich potential future research imagination, this paper reviews for online food shopping features, offers a commentary, and proposes future research directions. The propositions include the following: 1: the design and implementation of online food shopping (eco)systems should engage the consumers and other stakeholders to co-create collective and social values; 2: A better fit between technologies’ and food businesses’ natures could generate better applications for online food shopping; 3: A business model with sound finance systems becomes the core of a healthy online food ecosystem; 4: The interaction and transformation between online (virtual) and offline (virtual) food businesses determines the dynamic development of future food shopping.